SALACCA-TAN: Bioactive Gel Formulation Based on Snake Fruit Seed Waste (Salacca zalacca) as an Environmentally Friendly Dual-Function Antioxidant and Protease Inhibitor Agent - Khadijah Althafunnisa; Aliifah Yumna; Syafira Dian Noor (Sean Institute, 2026)
The increase in tropical fruit waste in Indonesia poses a challenge to sustainable resource management. One potential waste product is salak seeds (Salacca zalacca), which are rich in antioxidant compounds. This study aims to utilise salak seed extract as an active ingredient in environmentally friendly antioxidant gels based on sodium carboxymethyl cellulose (Na-CMC). The extract was obtained through maceration in 70% ethanol and formulated into three variants: a control gel without extract, and gels with 5 mL and 8 mL of extract. The formulation tests included pH, homogeneity, spreadability, organoleptic properties, and apple browning test. The results showed a pH of 5.5-5.8 (in accordance with skin pH), homogeneous texture, and light brown colour with a distinctive salak seed aroma that was liked by the panelists. Spreadability increased from 2.5 cm (control) to 2.8 cm (5 mL) and 3.0 cm (8 mL). The gel with 8 mL extract was also most effective in inhibiting enzymatic browning in apples, indicating high antioxidant activity. With good physical stability and antioxidant efficacy, salak seed extract gel has the potential to be developed as a natural cosmetic product and green biotherapeutic innovation based on local waste.